2016
DOI: 10.1016/j.fertnstert.2016.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Limitations and barriers in access to care for male factor infertility

Abstract: The primary challenge to identifying and addressing barriers in access to care for male factor infertility is accurate measurement of the prevalence of male infertility. Current estimates are based on couples pursuing assisted reproduction, and likely underestimate the problem. These estimates also fail to account for the number of patients facing infertility due to cancer or cancer treatment. Lack of health insurance coverage for the diagnosis and treatment of infertility presents a major barrier for couples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 51 publications
1
60
0
1
Order By: Relevance
“…Infertility affects nearly 50 million couples in reproductive age worldwide, and male factor contributes to approximately 50% of these cases (Agarwal et al ., ). Male infertility can be attributed to multiple factors, although sperm dysfunction (and particularly defects in sperm motility) is one of the most common causes of male infertility (Mascarenhas et al ., ; Kumar & Singh, ; Mehta et al ., ). To date, male infertility diagnosis is mainly based on the results of standard semen analysis; however, nearly one‐third of men with normal values in routine semen parameters are unable to achieve pregnancy revealing the limited value of this analysis as a diagnostic tool (Ray et al ., ; Pizzol et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Infertility affects nearly 50 million couples in reproductive age worldwide, and male factor contributes to approximately 50% of these cases (Agarwal et al ., ). Male infertility can be attributed to multiple factors, although sperm dysfunction (and particularly defects in sperm motility) is one of the most common causes of male infertility (Mascarenhas et al ., ; Kumar & Singh, ; Mehta et al ., ). To date, male infertility diagnosis is mainly based on the results of standard semen analysis; however, nearly one‐third of men with normal values in routine semen parameters are unable to achieve pregnancy revealing the limited value of this analysis as a diagnostic tool (Ray et al ., ; Pizzol et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…A review of 33 studies revealed that women had more negative experiences with infertility than men in many domains, such as depression, anxiety, stigmatization, self-esteem, stress, and identity (Casu & Gremigni, 2016;Ying, Wu, & Loke, 2016). However, male infertility has historically been an overlooked problem (Ahmadi, Montaser-Kouhsari, Nowroozi, & Bazargan-Hejazi, 2011;Mehta, Nangia, Dupree, & Smith, 2016). In some societies, infertile men are stigmatized as futile and useless, because children are highly valued for socio-cultural and economic reasons and the lack of an heir is the gravest offense against filial piety (Ahmadi et al, 2011;Alhassan, Ziblim, & Muntaka, 2014;Lee & Chu, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…There are multiple epidemiologic, geographic, epistemic, financial, socioeconomic, and policy-based barriers that, compounded with our lack of knowledge, make it challenging for men to obtain high-quality infertility care [37]. One barrier to men seeking infertility treatment is that male specialists (andrologists) are not usually part of the infertility treatment team.…”
Section: There Are Many Barriers To Male Infertility Diagnosis and Trmentioning
confidence: 99%